Reassessing North-South relations: the case of North-South preferential trade agreements. Issue 1 (21st March 2016) - Sahakyan, Davit
Abstract : Purpose: The purposes of this paper are to provide a new framework for the (re)assessment of North-South relations, with a specific focus on North-South preferential trade agreements (PTAs); advance a new mechanism of how first-order, i.e. Southern countries' first, North-South PTAs can affect the outcomes of second-order, i.e. Southern countries' subsequent, North-South PTA negotiations; and re-examine the effects of North-South power asymmetries on the outcomes of North-South PTA negotiations. Design/methodology/approach: The paper focuses on how North-South power asymmetries affect the outcomes of North-South PTA negotiations. It introduces the concept of "first-order" and "second-order" North-South PTAs to show that the "order" of an agreement can be a crucial factor in PTA negotiations. The claims of the paper are also supported by primary data obtained through the author's personal interviews with European Union and USA trade officials and policy-makers (seeAppendix ). Findings: The paper advances a new theoretical framework that takes a longer-term view on North-South trade relations, whereby, against the backdrop of the proliferating PTAs, first-order North-South agreements can raise the bargaining powers of Southern countries during subsequent North-South PTA negotiations, with strong implications for both developed and developing countries. Research limitations/implications: The paper is largely theoretical. A systematic empirical study of North-South PTAs will be required to validate or refute the theoretical framework advanced in this paper. Originality/value: The paper introduces a new variable, namely the "order" of an agreement, which affects the logic of North-South PTA negotiations. Hence, the paper sets out a new theoretical framework that allows for a more accurate assessment of North-South power asymmetries and their effects on the outcomes of North-South PTA negotiations.